Sestig jaar se mynteenmaatreëlswerk in die Suid-Afrikaanse vloot, 1947-2007 (3): op weg na en in die nuwe Suid-Afrika, 1990-2007 - Wessels, André (Faculty of Humanities, University of the Free State, 2010)
The year 1990 set in motion a train of political events that led to the Republic of South Africa’s first-ever truly democratic elections in 1994, which, in turn, led to the country’s readmittance to the international community, and the opening up of new diplomatic and other opportunities. In the meantime, the then South African Defence Force underwent a process of rationalisation in the wake of the end of its involvement in the Namibian War of Independence and in the civil war in Angola, and in due course was amalgamated with other military forces to form the new South African National Defence Force. In this, the third and last article of a three-part study of mine-countermeasures (MCM) in the South African Navy during the years 1947 to 2007, a review is given of the work done by the Navy’s MCM vessels from 1990 to 2007; i.e. by the four “River” class minehunters and the last four remaining “Ton” class minesweepers, as well as by the Type 351 minesweepers that replaced the “Tons” in 2001. Special emphasis will be placed on local as well as overseas flag-showing visits, and the importance of MCM for the South African Navy will also be evaluated.
Keywords: Mine-countermeasures; South African Navy, 1947-2007; Mine-countermeasure vessles